Local stepwise groups with complementable infinite nonprimary subgroups - Mishchenko , В. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The investigations of infinite groups with certain systems of complemented infinite subgroups, suggested by Chernikov, are continued. It is proved that an infinic locally graduated, nonprimary group with complemented infinite nonprimary subgroups is locally finite and solvable, and all of its nonprimary subgroups have complements if and only if it is not Chernikov.